Penerapan Arsitektur Modern pada Perencanaan Apartemen Di Kota Kendari - Syukur Syukur; Hapsa Rianty; Yudhi Dwi Hartono (Arsitektur Universitas Muhammadiyah Kendari, 2021)
Kendari City is one of the developing cities in Indonesia with a modern type of society that tends to expect practicality and time efficiency. A typical society like this needs to be accommodated by the existence of vertical housing. Phenomena and opportunities like this need to be addressed wisely by the local government and business people in the property sector. Therefore, the City of Kendari needs to plan a residence that is arranged vertically in this case an apartment as a solution to the current high demand for housing. To be able to plan a good apartment, this study uses a descriptive qualitative method combined with a quantitative approach. Based on the results of location and site analysis, this apartment building is planned to be built in Kadia District, Kendari City. The concept or theme applied to the planning of this building is a modern concept that is the unity and characteristic of apartment buildings. With the planning and design of an apartment building with a modern concept, it is hoped that this apartment can meet the needs of the community as an upper middle class residence and become a new Landmaerk in Kendari City.